Distinguishing Hepatocellular Carcinoma From Hepatic Inflammatory Pseudotumor Using a Nomogram Based on Contrast-Enhanced Ultrasound - Liao, Mengting; Wang, Chenshan; Zhang, Bo; Jiang, Qin; Liu, Juan; Liao, Jintang (Frontiers in Oncology, 2021)
Background: Hepatocellular carcinoma (HCC) and hepatic inflammatory pseudotumor (IPT) share similar symptoms and imaging features, which makes it challenging to distinguish from each other in clinical practice. This study aims to develop a predictive model based on contrast-enhanced ultrasound (CEUS) and clinical features to discriminate HCC from IPT. Methods: Sixty-two IPT and 146 HCC patients were enrolled in this study, where pathological diagnosis was served as the reference standard for diagnosis. Clinical and ultrasound imaging data including CEUS features: enhancement during arterial phase, portal phase and delayed phase, description of enhancement, early washout within 60s, feeding artery, peritumoral vessels, peritumoral enhancement and margin of non-enhanced area were retrospectively collected. Imaging data were reviewed by two experienced ultrasound doctors. Patients were randomly assigned to training and validation sets. Chi-squared test followed by LASSO regression was performed on ultrasonographic features in the training set to identify the most valuable features that distinguish HCC from IPT, based on which the sonographic score formula was generated. With the significant clinical and ultrasonographic indicators, a nomogram was developed. The performance of the nomogram was verified by ROC curve and decision curve analysis (DCA) with the comparison to sonographic score and the ultrasound doctor’s diagnosis. Results: The most valuable ultrasonographic features that distinguish between HCC and IPT were arterial phase enhancement, early washout, peritumoral vessels, peritumoral enhancement and liver background. The sonographic score based on these features was verified to be an independent factor that predicts the diagnosis (P=0.003). Among the clinical indicators, AFP (P=0.009) and viral hepatitis infection (P=0.004) were significant. Sonographic score, AFP and viral hepatitis were used to construct a predictive nomogram. The AUC of the nomogram was 0.989 and 0.984 in training and validation set respectively, which were higher than those of sonographic score alone (0.938 and 0.958) or the ultrasound doctor’s diagnosis (0.794 and 0.832). DCA showed the nomogram provided the greatest clinical usefulness. Conclusion: A predictive nomogram based on a sonographic signature improved the diagnostic performance in distinguishing HCC and IPT, which may help with individualized diagnosis and treatment in clinical practice.